2018
DOI: 10.1002/ps.5201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clothianidin‐treated seed on the arthropod community in a mid‐Atlantic no‐till corn agroecosystem

Abstract: Clothianidin primarily influenced arthropod communities during the 4 weeks following planting, with disruptions to major natural enemy taxa, but communities showed trends toward recovery at the later corn stages. While the insecticide suppressed multiple herbivores, none were economically damaging to corn; thus, the pest suppression benefits of clothianidin observed in this study did not justify the non-target impacts. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 88 publications
(189 reference statements)
3
21
0
Order By: Relevance
“…Additionally, it has been suggested that individual studies of pesticide non-target impacts lack the power to detect effects due to relatively small sample size and high variability in arthropod community datasets (Douglas & Tooker, 2016). A meta-analysis across 20 studies revealed small negative effects [effect size d = −0.30 ± 0.10 (95% confidence interval)] on natural enemy abundance associated with NSTs, with a trend towards soil taxa being more impacted than foliar taxa (Douglas & Tooker, 2016 we expected foliar communities to recover rapidly, as observed by Disque et al (2018) in maize. In contrast, PRC analysis for sticky cards showed increasing deviations from the control community over time in insecticide-treated winter wheat and for all pesticide treatments in maize, with no recovery over the sampling period.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodsmentioning
confidence: 68%
See 3 more Smart Citations
“…Additionally, it has been suggested that individual studies of pesticide non-target impacts lack the power to detect effects due to relatively small sample size and high variability in arthropod community datasets (Douglas & Tooker, 2016). A meta-analysis across 20 studies revealed small negative effects [effect size d = −0.30 ± 0.10 (95% confidence interval)] on natural enemy abundance associated with NSTs, with a trend towards soil taxa being more impacted than foliar taxa (Douglas & Tooker, 2016 we expected foliar communities to recover rapidly, as observed by Disque et al (2018) in maize. In contrast, PRC analysis for sticky cards showed increasing deviations from the control community over time in insecticide-treated winter wheat and for all pesticide treatments in maize, with no recovery over the sampling period.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodsmentioning
confidence: 68%
“…In foliar sweep net and visual samples from soybeans, we also observed reduced abundance or activity density of lady beetles (Coccinellidae), which are known to be impacted by neonicotinoids (Amjad, Azam, Sarwar, Malik, & Sattar, 2018;Disque et al, 2018;Zhang et al, 2016), as well as predatory thrips; some of these impacts occurred across all three pesticide treatments and thus may have been driven by the fungicide treatments. In contrast, spider abundance was higher in the maize visual samples from the insecticide-treated plots, and to a lesser extent the fungicide-treated plots.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodsmentioning
confidence: 70%
See 2 more Smart Citations
“…Increased taxon diversity and evenness is associated with reduced pest pressure (Lundgren & Fausti, 2015); therefore, community-level impacts of NSTs could disrupt natural pest control. In maize, clothianidin treated seed disturbed the overall arthropod community after planting, with several beneficial predators decreasing in abundance (Disque, Hamby, Dubey, Taylor, & Dively, 2018). Neonicotinoids can also negatively impact pollinators (Godfray et al, 2014).…”
Section: Introductionmentioning
confidence: 99%